2018
DOI: 10.1080/09649069.2018.1493651
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating integrative services in edge-of-care work

Abstract: Children living on 'the edge-of-care' are typically known to local safeguarding authorities and are considered likely to face risks to their safety. Many are subject to a child protection plan and/or involved in 'pre-proceedings' processes. A growing number of their parents face (un)diagnosed mental health difficulties as well as economic and social precarity. This article draws on a mixed methods evaluation of a pilot service in the East of England offering a therapeutically-led attachmentbased intervention f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…These findings could be made available to general practitioners and other professionals to highlight the potential value in referring women to these specialist services. There is some evidence to suggest that parent-infant psychology may be particularly promising for improving infant attachment security in high-risk families (Barlow, Bennett, Midgley, Larkin, & Wei, 2015), and that a higher proportion of children are able to stay in the family home when mothers receive intense trauma-informed support (McPherson et al, 2018). Further research is needed to explore in more detail experiences and effectiveness of interventions that support parenting and the mother-infant relationship in women with complex and intersecting needs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be made available to general practitioners and other professionals to highlight the potential value in referring women to these specialist services. There is some evidence to suggest that parent-infant psychology may be particularly promising for improving infant attachment security in high-risk families (Barlow, Bennett, Midgley, Larkin, & Wei, 2015), and that a higher proportion of children are able to stay in the family home when mothers receive intense trauma-informed support (McPherson et al, 2018). Further research is needed to explore in more detail experiences and effectiveness of interventions that support parenting and the mother-infant relationship in women with complex and intersecting needs.…”
Section: Discussionmentioning
confidence: 99%
“…This is significant because it suggests that women who have had children removed in the past can be supported to parent safely. Studies of 'early' family-based interventions linked to parent-infant mental health interventions and Family Drug and Alcohol Court (FDAC) programmes have similarly found that interdisciplinary work targeting individual needs can enable mothers previously deemed unable to parent, to develop anew their capacity to parent and to keep subsequent babies [7,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Between them, these new services engage with hundreds of families each year. Published peer reviewed studies of service effectiveness in this field remain relatively rare, however, with only two available to date [6,7]. This article offers the first combined analysis of independent evaluations of three of these new RCP services in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, existing literature outlines steps authors can take to ensure qualitative evidence is synthesized with sufcient rigour, whilst maintaining the context and meaning present in individual studies [46]. Whilst existing reviews focus on parents with mental health needs [47] or those with child protection concerns [29], families with both mental health and children's social services involvement have a distinct set of needs which singlefocus interventions often neglect [48]. Te nature, structure, and names of these services difer between contexts, but for the purpose of this review, we will use "children's social services" to mean services designed to support and protect vulnerable children.…”
Section: Introductionmentioning
confidence: 99%